Effects of transcranial electrical stimulation of the cerebellum, parietal cortex, anterior cingulate, and motor cortex on postural adaptation - Nastaran Bahadorani; Roya Khanmohammadi (Scientific Reports)
Abstract Several cortical regions, such as the cerebellum, posterior parietal cortex (PPC), anterior cingulate cortex (ACC), and primary motor cortex (M1), play critical roles in postural adaptation. However, studies examining the effects of transcranial direct current stimulation (tDCS) on postural adaptation in healthy individuals are limited and often yield inconsistent findings, making it challenging to draw definitive conclusions. Most research has focused on individual brain regions, leaving a gap in understanding how the cerebellum, PPC, ACC, and M1 differentially contribute to postural adaptation. Identifying the most effective brain regions for postural adaptation could optimize rehabilitation strategies for individuals with postural control impairments. Thus, this study compared the effects of tDCS over these specific brain regions on postural adaptation. This parallel, randomized, double-blinded, controlled trial involved 75 participants, divided into five groups: anodal stimulation of the PPC, cerebellum, M1, ACC, or a sham group. Each group received 20 min of direct current stimulation in a single session. Center of pressure (COP) displacement, path length, velocity, and standard deviation (SD) were measured across three trials in the anteroposterior (AP) direction during standing disturbed using vibrators attached to bilateral Achilles tendons. A repeated measure ANOVA was used to assess within-group effects, while one-way ANOVA compared between-group differences. Between-group analysis did not reveal statistically significant differences during both the vibration and post-vibration phases. Nonetheless, the within-group analysis revealed significant enhancements in postural adaptation for the PPC and cerebellum groups during the vibration phase. Specifically, the PPC group demonstrated significant reductions in COP displacement (P = 0.005), path length (P = 0.018), and SD of COP displacement (P = 0.045) across trials. Similarly, in the cerebellar group, significant improvements were noted in COP displacement (P = 0.044), velocity (P = 0.006), and phase plane (P = 0.016) across trials. In contrast, no significant changes were found in the M1, ACC, or sham groups during either the vibration or post-vibration phases. In conclusion, while intergroup comparisons were not significant, intra-group analysis revealed that PPC and cerebellar stimulation significantly enhanced postural adaptation. Incorporating tDCS over the PPC or cerebellum in postural training programs could improve postural control, potentially reducing fall risk in clinical populations such as older adults or individuals with neurological dysfunction. RCT registration: On the Iranian Registry of Clinical Trials (IRCT20220819055745N1). Registration date: 15/11/2022.